NEW TECHNOLOGIES INCREASING THE HEALTHY LIFESTYLE OF STUDENTS IN PHYSICAL EDUCATION - Khamrakulov Tulkin Tohirovich; Sarukhanov Arsen Albertovich; Shokirov Shukhrat Gayratovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes the main directions and tools used in the modern system of higher education, and notes the introduction of innovative technologies in teaching practice. Under such conditions, new forms and methods of physical activity at the lessons of physical education of university students can contribute to the formation of a healthy lifestyle.